Photooxidation adsorbent for removing radioactive iodide and preparation method of photooxidation adsorbent

A photo-oxidation adsorbent with bismuth trioxide on a zirconium-based metal organic framework addresses the high cost and efficiency challenges of bismuth-based adsorbents, enhancing iodine removal by chemical and physical adsorption, achieving high adsorption capacity and rate.

CN119186528APending Publication Date: 2024-12-27NANJING UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411625931.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing bismuth-based adsorbents for radioactive iodine removal are hindered by high cost and the challenge of achieving high adsorption capacity and rate, necessitating a more efficient and cost-effective solution.

Method used

A photo-oxidation adsorbent is developed by depositing bismuth trioxide uniformly on a zirconium-based metal organic framework, utilizing both chemical and physical adsorption mechanisms to enhance iodine removal.

Benefits of technology

The adsorbent achieves improved iodine adsorption capacity and rate through a synergistic photo-oxidation process, effectively converting iodide ions into elemental iodine, with optimal bismuth trioxide loading ratios of 40%-70% by mass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186528A_ABST
    Figure CN119186528A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorbents, and discloses a photooxidation adsorbent for removing radioiodide and a preparation method thereof, the adsorbent comprises a zirconium-based metal organic framework, and bismuth trioxide is uniformly deposited on the surface of the zirconium-based metal organic framework. The obtained adsorbent can well adsorb iodine through the photooxidation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbents, and in particular to a photo-oxidation adsorbent for removing radioactive iodides and a preparation method thereof. Background Art

[0002] Nuclear energy is one of the most promising energy sources for humankind in the future. However, various radioactive fission products produced by nuclear fission pose a huge risk to the environment. 129 I is one of the typical radioactive nuclides with a half-life of 15.7 million years. What is worrying is that radioactive iodine will spread through the food chain, causing the risk of cancer and genetic diseases. The main form of radioactive iodine is iodide anion (I - ), has high water solubility and environmental mobility. Therefore, it is safe and reliable to treat radioactive iodine ions (I - ) is imminent.

[0003] To date, the use of solid adsorbents to adsorb radioactive iodine is the main strategy. - Bismuth-based materials have been widely studied due to their high selectivity, fast adsorption rate and stable adsorption. However, the high cost of silver hinders its practical application. - With high affinity, it is expected to be a substitute for silver. Designing a bismuth-based adsorbent with high adsorption capacity and adsorption rate for iodide ions remains a great challenge. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a photo-oxidation adsorbent for removing radioactive iodide and a preparation method thereof. The adsorbent obtained by the present invention can well adsorb iodine through photo-oxidation ability.

[0005] The invention provides a photo-oxidation adsorbent for removing radioactive iodide. The adsorbent comprises a zirconium-based metal organic framework, on the surface of which bismuth trioxide (Bi2O3) is uniformly deposited.

[0006] Furthermore, based on mass, bismuth trioxide / (zirconium-based metal organic framework+bismuth trioxide) is 40%-70%.

[0007] The present invention also provides a method for preparing the photo-oxidation adsorbent for removing radioactive iodide, the method comprising: The zirconium-based metal organic framework and the bismuth source are dissolved and dispersed, and then a glycine solution is added dropwise to obtain a mixed solution. The mixed solution is subjected to a hydrothermal reaction and washed to obtain an adsorbent for depositing bismuth trioxide on the surface of the zirconium-based metal organic framework.

[0008] Furthermore, deionized water is used to dissolve and disperse the zirconium-based metal organic framework and the bismuth source.

[0009] Furthermore, after the zirconium-based metal organic framework and the bismuth source are dissolved and dispersed, the molar concentration of the bismuth source in the dispersed solution is 1 mmol / 20 mL based on the bismuth ions in the bismuth source.

[0010] Furthermore, based on mass, bismuth trioxide / (zirconium-based metal organic framework+bismuth trioxide) is 40%-70%.

[0011] In the present invention, the mass of bismuth trioxide is determined by the bismuth source, and the bismuth trioxide is determined by determining the molar amount of bismuth ions in the bismuth source and the relative molecular mass of the bismuth trioxide.

[0012] Furthermore, the bismuth source includes one or more of bismuth nitrate and bismuth nitrate pentahydrate.

[0013] Furthermore, the molar concentration of glycine in the glycine solution is 1 mmol / 10 mL.

[0014] Furthermore, the preparation method of the glycine solution is to dissolve glycine in deionized water.

[0015] Furthermore, the volume ratio of the solution in which the zirconium-based metal organic framework and the bismuth source are dissolved and dispersed to the glycine solution is 4:3.

[0016] Furthermore, the temperature of the hydrothermal reaction is 130°C-150°C, and the time of the hydrothermal reaction is 23h-25h.

[0017] Furthermore, the specific method of washing includes washing with ethanol and deionized water at least three times in sequence.

[0018] Those skilled in the art may use anhydrous ethanol or ethanol solutions of other concentrations when washing, as long as the purpose can be achieved.

[0019] Furthermore, the zirconium-based metal organic framework is MOF-808.

[0020] Furthermore, the preparation method of the zirconium-based metal organic framework comprises: Add trimesic acid (H3BTC) and zirconium oxychloride octahydrate into an organic solvent, mix them evenly, perform hydrothermal reaction, and wash.

[0021] Furthermore, the organic solvent consists of formic acid and N,N-dimethylformamide, and the volume ratio of formic acid to N,N-dimethylformamide is 1:1.

[0022] Furthermore, the molar ratio of trimesic acid to zirconium dichloride octahydrate is 1:1.

[0023] Furthermore, the molar concentration of trimesic acid in the organic solvent is 1 mmol / 60 mL.

[0024] Furthermore, the uniform mixing method may be ultrasonic, and stirring may be performed during the ultrasonic process. As an example, the stirring time is 0.5 h.

[0025] Furthermore, the temperature of the hydrothermal reaction is 100° C.-120° C., and the time of the hydrothermal reaction is 11 h-13 h.

[0026] Furthermore, the specific method of washing is to use N,N-dimethylformamide and deionized water to wash at least three times in sequence.

[0027] The present invention also provides the use of the photo-oxidation adsorbent for removing radioactive iodide in adsorbing iodine.

[0028] Furthermore, the adsorption method uses photo-oxidation to adsorb iodine.

[0029] The embodiments of the present invention have the following technical effects: 1. In the present invention, the adsorbent can undergo photo-oxidation effect. Under the photo-oxidation effect, I - After being photooxidized to form I2, the zirconium-based metal organic framework adsorbs the generated iodine element inside the zirconium-based metal organic framework, thereby improving the physical adsorption capacity of the adsorbent; on this basis, the zirconium-based metal organic framework is loaded with bismuth trioxide, which can chemically adsorb iodine ions in the form of Bi4O5I2 on the surface of δ-Bi2O3. The iodine adsorbent of the present invention achieves the adsorption of iodine ions by chemical and physical methods.

[0030] 2. In the present invention, in order to further enhance the adsorption capacity of iodide ions, the adsorption amount of bismuth trioxide on the surface of the zirconium-based metal-organic framework is further controlled. An appropriate amount of bismuth trioxide loading can not only facilitate the exposure of the active sites of the adsorbent, but also reduce the agglomeration effect and expose the adsorption sites of the zirconium-based metal-organic framework, thereby facilitating further enhancement of the adsorption effect of the adsorbent. Therefore, bismuth trioxide / (zirconium-based metal-organic framework+bismuth trioxide) is further selected to be 40%-70% by mass. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 is the characterization data provided by the embodiments and comparative examples of the present invention, wherein Figure 1 a is the XRD spectra of the embodiments and comparative examples, Figure 1 b is the FT-IR spectra of the embodiments and comparative examples, Figure 1 c is the N2 adsorption-desorption isotherm diagram of the embodiment and the comparative example, Figure 1 d in the figure is the Bi 4f high-resolution spectrum of the embodiment and the comparative example, Figure 1 e is the Zr 3d high-resolution spectrum of the embodiment and the comparative example, Figure 1 Fig. f is the ESR spectrum of the embodiment and the comparative example.

[0033] Figure 2 is the SEM picture of the embodiment and the comparative example, wherein Figure 2 a is the SEM image of comparative example 1. Figure 2 b is the SEM picture of comparative example 2. Figure 2 Figure c is the SEM image of Example 3. Figure 2 d in FIG. 3 is the HRTEM image of Example 3. Figure 2 e in FIG. is the HRTEM image of Example 3, Figure 2 f in is the SAED image of Example 3, Figure 2 g in FIG. 3 is the HRTEM-EDS image of Example 3. Figure 2 h in is the distribution diagram of Bi element in Example 3, Figure 2 i in is the distribution diagram of O element in Example 3, Figure 2 j in is the distribution diagram of the C element in Example 3, Figure 2 The k in FIG. 3 is the distribution diagram of the Zr element in Example 3.

[0034] Figure 3 : is a test result diagram of the embodiment and the comparative example, wherein Figure 3 a in the middle is the test result of isothermal adsorption experiment. Figure 3 Figure b is the result of adsorption kinetics test. Figure 3 Figure c is the test result of photo-oxidation-adsorption synergistic experiment. Figure 3 d is the result of the photo-oxidation kinetics experiment (C0(I - ) = 500mg / L), Figure 3 The number e in the figure is the iodine ion removal rate experiment.

[0035] Figure 4 1 is a graph showing the test results of the embodiments and comparative examples, wherein Figure 4 a is the iodine ion removal experiment at different pH values ​​in Example 3. Figure 4 b is the Zeta potential at different pH values ​​in Example 3, Figure 4c in Example 3 in different competitive ion adsorption experiments (C0(I - ) = 500mg / L, the competitive ion concentration is 2mmol / L), Figure 4 d in the figure is the experimental test result of iodine ion removal of the embodiment and the comparative example, Figure 4 e in the middle is the result of gamma ray irradiation experiment, Figure 4 The middle f is the stability test after adsorption.

[0036] Figure 5 is the test result of the embodiment, wherein Figure 5 a is the XRD diagram of Example 3 before and after adsorption, Figure 5 Figure b is the Bi 4f diagram before and after photo-oxidation adsorption in Example 3. Figure 5 Figure c is the O 1s diagram before and after photo-oxidation adsorption in Example 3. Figure 5 Figure d in the figure is the I 3d diagram before and after photo-oxidation adsorption in Example 3. Figure 5 In the figure e, it is the Raman spectrum. Figure 5 f is the ESR spectrum. Figure 5 g in the figure is the SEM image after adsorption in Example 3. Figure 5 h in is the HRTEM image after adsorption in Example 3, Figure 5 i in FIG. 1 is the SAED image after adsorption in Example 3, Figure 5 j in the figure is the HRTEM-EDS image after adsorption in Example 3. Figure 5 The k in FIG. 1 is the distribution diagram of Bi element after adsorption in Example 3. Figure 5 1 in the figure is the C element distribution diagram after adsorption in Example 3, Figure 5 Where m is the distribution diagram of I element after adsorption in Example 3, Figure 5 n in is the distribution diagram of O element after adsorption in Example 3, Figure 5 O in FIG. 1 is the Zr element distribution diagram after adsorption in Example 3.

[0037] Figure 6 is a Zr 3d diagram of an embodiment. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0039] In a first aspect, some embodiments of the present invention provide a photo-oxidative adsorbent for removing radioactive iodide, wherein the adsorbent comprises a zirconium-based metal-organic framework, and bismuth trioxide is uniformly deposited on the surface of the zirconium-based metal-organic framework.

[0040] In some embodiments, the ratio of bismuth trioxide to (zirconium-based metal organic framework + bismuth trioxide) is 40%-70% by mass.

[0041] In a second aspect, some embodiments of the present invention also provide a method for preparing the photo-oxidation adsorbent for removing radioactive iodide, the preparation method comprising: The zirconium-based metal organic framework and the bismuth source are dissolved and dispersed, and then a glycine solution is added dropwise to obtain a mixed solution. The mixed solution is subjected to a hydrothermal reaction and washed to obtain an adsorbent for depositing bismuth trioxide on the surface of the zirconium-based metal organic framework.

[0042] In some embodiments, deionized water is used to dissolve and disperse the zirconium-based metal organic framework and the bismuth source.

[0043] In some embodiments, after the zirconium-based metal organic framework and the bismuth source are dissolved and dispersed, the molar concentration of the bismuth source in the dispersed solution is 1 mmol / 20 mL based on the bismuth ions in the bismuth source.

[0044] In some embodiments, the ratio of bismuth trioxide to (zirconium-based metal organic framework + bismuth trioxide) is 40%-70% by mass.

[0045] In some embodiments, the bismuth source includes one or more of bismuth nitrate and bismuth nitrate pentahydrate.

[0046] In some embodiments, the molar concentration of glycine in the glycine solution is 1 mmol / 10 mL.

[0047] In some embodiments, the volume ratio of the solution in which the zirconium-based metal organic framework and the bismuth source are dissolved and dispersed to the glycine solution is 4:3.

[0048] In some embodiments, the temperature of the hydrothermal reaction is 130° C.-150° C., and the time of the hydrothermal reaction is 23 h-25 h.

[0049] In some embodiments, the specific method of washing includes washing with ethanol and deionized water at least three times in sequence.

[0050] In some embodiments, the zirconium-based metal organic framework is MOF-808.

[0051] In some embodiments, the method for preparing the zirconium-based metal organic framework comprises: Add trimesic acid and zirconium oxychloride octahydrate into an organic solvent, mix evenly, perform hydrothermal reaction, and wash.

[0052] In some embodiments, the organic solvent consists of formic acid and N,N-dimethylformamide, and the volume ratio of formic acid to N,N-dimethylformamide is 1:1.

[0053] In some embodiments, the molar ratio of trimesic acid to zirconium oxychloride octahydrate is 1:1.

[0054] In some embodiments, the molar concentration of trimesic acid in the organic solvent is 1 mmol / 60 mL.

[0055] In some embodiments, the uniform mixing may be carried out by ultrasound, and stirring is performed during the ultrasound process. As an example, the stirring time is 0.5 h.

[0056] In some embodiments, the temperature of the hydrothermal reaction is 100° C.-120° C., and the time of the hydrothermal reaction is 11 h-13 h.

[0057] In some embodiments, the specific method of washing is to use N,N-dimethylformamide and deionized water to wash at least three times in sequence.

[0058] In a third aspect, some embodiments of the present invention also provide the use of the photo-oxidation adsorbent for removing radioactive iodide in adsorbing iodine.

[0059] The following is described in conjunction with some specific embodiments and comparative examples: Embodiment 1: Preparation of zirconium-based metal organic framework: 1mmol of trimesic acid (H3BTC) and 1mmol of zirconium dichloride octahydrate (ZrOCl2·8H2O) were added to a mixed solution of 60mL formic acid and N,N-dimethylformamide, wherein the volume ratio of formic acid to N,N-dimethylformamide was 1:1. The solution was dispersed with ultrasound and stirred for more than 0.5 hours until completely mixed. The solution was then transferred to a reactor and heated at 110°C for 12 hours. The washing solvent was N,N-dimethylformamide and deionized water for three times; Preparation of adsorbent: 1.54 g of the prepared zirconium-based metal-organic framework and 2 mmol (0.97 g) of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) were dissolved in 40 mL of deionized water, referred to as solution a. 10 mmol (0.75 g) of glycine was added to 30 mL of deionized water, referred to as solution B. Subsequently, solution B was slowly dripped into solution a. The solution was transferred to a reactor and heated at 140 °C for 24 h. Finally, the sample was washed three times with ethanol and deionized water. Recorded as: 40-Bi / M.

[0060] Embodiment 2: The preparation method of Example 2 is the same as that of Example 1, but the added mass of the zirconium-based metal organic framework in Example 2 is 1.03 g, which is recorded as: 50-Bi / M.

[0061] Embodiment 3: The preparation method of Example 3 is the same as that of Example 1, but the added mass of the zirconium-based metal organic framework in Example 3 is 0.69 g, which is recorded as: 60-Bi / M.

[0062] Embodiment 4: The preparation method of Example 4 is the same as that of Example 1, but the added mass of the zirconium-based metal organic framework in Example 4 is 0.44 g, which is recorded as: 70-Bi / M.

[0063] Comparative Example 1: 0.1 g of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dissolved in 40 mL of deionized water, referred to as solution a. 10 mmol (0.077 g) of glycine was added to 30 mL of deionized water, referred to as solution B. Subsequently, solution B was slowly dripped into solution a. The solution was transferred to a reactor and heated at 140 °C for 24 hours. Finally, the sample was washed three times with ethanol and deionized water. Recorded as: δ-Bi2O3.

[0064] Comparative Example 2: 1 mmol of trimesic acid (H3BTC) and 1 mmol of zirconium dichloride octahydrate (ZrOCl2·8H2O) were added to a mixed solution of 60 mL of formic acid and N,N-dimethylformamide, wherein the volume ratio of formic acid to N,N-dimethylformamide was 1:1. The solution was dispersed with ultrasound and stirred for more than 0.5 hours until completely mixed. The solution was then transferred to a reactor and heated at 110°C for 12 hours. The washing solvent was N,N-dimethylformamide and deionized water for three times. Note: MOF-808.

[0065] The present invention also tests the performance of the adsorbent obtained from the embodiments and comparative examples: (1) Characterization of the embodiments and comparative examples: X-ray diffraction (XRD) patterns were recorded between 20° and 70° on a Bruker AXS (D8 Advance) diffractometer using Cu Kα radiation at 40 kV and 30 mA. Specific surface area and porosity measurements were tested by nitrogen adsorption and desorption analyzer (BELSORP-MAX) using Barrett-Emett-Teller (BET) and Barrett-Joyner-Halenda (BJH) calculations, respectively. The chemical composition and valence state of the catalyst surface were analyzed using X-ray photoelectron spectroscopy (XPS, Thermo Kalpha) with an Al Kα radiation source, and the binding energy was calibrated with the C1s peak at 284.8 eV. Fourier transform infrared spectroscopy (FTIR) was performed on a Nicolet-iS50 spectrometer (Thermo, USA) in the wavenumber range of 4000–400 cm -1 , resolution 0.4cm -1 , using KBr pellets. Raman spectra were recorded using a Nicolet Almega dispersive Raman spectrometer (λex = 532 nm). Scanning electron microscopy (SEM) was performed on a JSM-7800F PRIME operated at 15 kV. Transmission electron microscopy (TEM) and high-resolution TEM (HRTEM) were performed on a FEI Tecnai F20 electron microscope operated at 200 kV accelerating voltage. Energy dispersive X-ray spectroscopy (EDX) measurements were performed on a Tecnai F210 electron microscope operated at 200 kV acceleration. Room temperature electron spin resonance (ESR) spectroscopy was performed using a JEOL JES-FA200 ESR spectrometer (300 K, 9.062 GHz). UV–visible absorption spectra were obtained on an Evolution 220 spectrometer. Zeta potential at different pH values ​​was determined using Zeta View (Particle Metrix, DE) in 0.5 g / L well-dispersed adsorbent powder suspensions at different pH values. The band gaps of the samples were measured by ultraviolet-visible diffuse reflectance spectroscopy (UV-vis.DRS) using a PERKIN ELMER Lambda 650S spectrophotometer, in which barium sulfate was used as a reference.

[0066] (2) Detailed information of electrochemical measurements: Electrochemical measurements were performed on an electrochemical workstation (CHI 850D). The mixed solution, Pt electrode, and Ag / AgCl electrode were used as electrolyte, auxiliary electrode, and reference electrode, respectively. The mixed solution was prepared from K3[Fe(CN)6] (0.1646 g), potassium chloride (0.7455 g), and deionized water (100 mL). 3 mg of the sample was added to the mixed solution (0.5 mL of ethanol and 20 μL of Nafion solution) and ultrasonically treated for 30 min. 30 μL of the mixed solution was dropped on fluorine-doped tin oxide (FTO, 1×2 cm 2 ) as the working electrode. The transient photocurrent response was measured at an open circuit voltage of 0.26 V. EIS was performed at 10 -1 -10 5 Hz frequency range, the amplitude was 5mV when the open circuit voltage was 0.23V. MS was at 2×10 3 The measurement was carried out at a frequency of Hz, with an open circuit pressure of 0.5V and a closed circuit voltage of -2V with an amplitude of 5mV.

[0067] (3) Adsorption isotherm experiment: 20 mg of adsorbent was added to 20 mL of I - In aqueous solution, I - The initial concentrations of the solutions were 50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 mg / L, 300 mg / L, 350 mg / L, 400 mg / L, 450 mg / L and 500 mg / L, respectively. After stirring for about 5 hours, 2 mL of the turbid solution was taken and filtered with a 0.22 μm membrane filter. The residual I in the solution after adsorption was measured and analyzed using an ultraviolet-visible spectrometer (UV-vis, Shimadzu-UV-2401PC, Japan) at 227 nm. - Concentration. The experimental data were fitted using the Langmuir model (Equation (1)) and the Freundlich model (Equation (2)) isotherm models;

[0068] where q c is the adsorption mass per unit weight of solid adsorbent, q m is the maximum adsorption capacity of the adsorbent (mg / g), C e is the equilibrium concentration of the adsorbate in the solution (mg / L), k1 is the Langmuir affinity constant. k2 and 1 / n are constants representing the adsorption capacity and adsorption strength, respectively.

[0069] (4) Adsorption kinetics experiment: The adsorption kinetics of iodide were evaluated by performing a batch test with an initial iodide concentration of 500 mg / L. 200 mg of the example and comparative example adsorbents were added to 200 mL of iodine containing 500 mg / L iodine under stirring. - Then, starting from the time when the adsorbent was added, 2 mL of the turbid solution was sampled periodically and filtered using a 0.22 μm membrane filter. The residual I in the solution after adsorption was measured and analyzed using a UV-visible spectrometer at 227 nm. - concentration;

[0070] The adsorption kinetics were evaluated by applying the following pseudo first-order kinetic equation (Eq. 3) and pseudo second-order kinetic equation (Eq. 4): where q t (mg / g) is the uptake capacity at time t (h). k1 and k2 (g / mg·min) are the rate parameters of the pseudo-first-order kinetic equation and pseudo-second-order kinetic equation, respectively.

[0071] (5) Photocatalytic experiment: Under stirring, add 200 mg of adsorbent to 200 mL of 500 mg / L - Concentration I - After 5 hours of dark adsorption, it was transferred to the photocatalytic reaction instrument and tested with a 300W xenon lamp as a simulated light source. During the test, the reaction solution (2 mL) was pipetted with a pipette and filtered with a 0.22 μm syringe filter. Two reaction solutions were taken from each sampling point for the determination of residual I - One of the reaction solutions was diluted 10 times to measure the residual I2 concentration. The residual I2 in the solution after adsorption was measured and analyzed using a UV-vis spectrometer at 227 nm and 523 nm. - and I2 concentration.

[0072] (6) Adsorption thermodynamics experiment: 20 mg of adsorbent was added to 20 mL of I - In aqueous solution, I -The initial concentrations of the solutions were 50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 mg / L, 300 mg / L, 350 mg / L, 400 mg / L, 450 mg / L and 500 mg / L, respectively. The solutions were stirred at 298.18 K, 308.18 K and 318.18 K for 5 hours, respectively. 2 mL of the turbid solution was taken and filtered with a 0.22 μm membrane filter. The residual I- concentration in the solution after adsorption was measured and analyzed using a UV-visible spectrometer at 227 nm. The changes in the thermodynamic parameters (ΔG, ΔH, ΔS) were determined by the following mathematical expressions:

[0073] Where ΔG (kJ·mol -1 ) is the Gibbs free energy change, ΔH (kJ•mol -1 ) is the enthalpy change, ΔS (J·mol -1 ·K -1 ) is the entropy change, R (8.314 J·mol -1 ·K -1 ) is the ideal gas constant, T (K) is the absolute temperature, and KL is the thermodynamic equilibrium constant. lnK L The linear plot as a function of 1 / T yields the enthalpy change (ΔH) and entropy change (ΔS) from the slope and intercept, respectively.

[0074] (7) Effect of pH value: The effect of pH on I - Eliminate the impact. Initial I - The concentration and adsorbent dosage were set to 500 mg / L. The pH value of the solution was adjusted by adding dilute HCl and NaOH. After stirring for 5 hours, 2 mL of the turbid solution was taken and separated using a 0.22 μm membrane filter. The remaining I in the supernatant was measured by UV-visible spectrophotometer at 227 nm. - concentration.

[0075] (8) Effect of competitive anions: By adding NO3 - , Cl - 、CO3 2- and SO4 2- The concentration of the competitive anion was used to evaluate the effect of the initial I - The concentration and sample dose were set to 500 mg / L and 1 g / L, respectively. -The molar ratio of 1:1 was 10:1. 20 mg of the sample was added to 20 mL of the mixed solution and stirred for 5 hours. Then 2 mL of the turbid solution was collected and filtered with a 0.22 μm membrane filter. The remaining I in the supernatant was measured by UV-visible spectrophotometer at 227 nm. - concentration.

[0076] Results and analysis: Table 1 Isotherm fitting parameters of Langmuir model and Freundlich model of Examples and Comparative Examples

[0077] Table 2 Kinetic parameters of iodine adsorption in Examples and Comparative Examples

[0078] The crystal structures of δ-Bi2O3, MOF-808 and Examples 1 to 4 of the present invention were determined by XRD. Figure 1 In (a), the diffraction peaks of the samples based on δ-Bi2O3 prepared in all examples are consistent with the characteristic diffraction peaks of cubic δ-Bi2O3 (JCPDS No. 27-0052). The characteristic peaks attributed to δ-Bi2O3 are sharp and intense, which indicates that the samples have high crystallinity. In addition, the XRD pattern of MOF-808 is consistent with that reported in the literature. [1] , confirming the crystal structure of MOF-808. In the spectra of Examples 1 to 4, as the mass proportion of δ-Bi2O3 in the adsorbent increases, the intensity of the two characteristic peaks of MOF-808 (8.47° and 8.84°) gradually decreases. This structural evidence shows that the preparation of δ-Bi2O3 and MOF-808 is successful and the preparation of the composite phase is effective.

[0079] The functional groups and molecular structures of δ-Bi2O3, MOF-808 and the examples were investigated by Fourier transform infrared spectroscopy, such as Figure 1 (b) In the spectrum of δ-Bi2O3, the -1 and 816cm -1 The characteristic peak of is attributed to the vibration of Bi-O bond, while the peak at 1029 cm -1 and 1290cm -1 The characteristic peaks are attributed to the stretching vibration of Bi-O-Bi bonds. In the spectrum of MOF-808, 646 cm -1 The peak at 754 cm is attributed to the vibration of Zr-O bonds, while the peak at 754 cm -1 The peak at 1375cm is attributed to the deformation and vibration of the CH bond (aromatic ring). -1 and 1441cm -1The peak at 1565 cm is attributed to the symmetric stretching of carboxylic acid, while the peak at 1565 cm -1 The peak at 1029 cm-1 is attributed to the vibration of the C=C double bond (benzene ring). -1 Move to 1044cm -1 , and the characteristic peak of Zr-O bond is from 646cm -1 Move to 649cm -1 , which may be due to the formation of Bi-O-Zr bonds in the heterojunction.

[0080] The specific surface area and pore size distribution of δ-Bi2O3, MOF-808 and the examples were studied by N2 adsorption-desorption isotherms. Figure 1 In (c), the isotherm of MOF-808 is a typical type I adsorption, reflecting the presence of micropores in the material. The isotherm of δ-Bi2O3 is a typical type V adsorption with a typical H3 type hysteresis loop, indicating the presence of mesopores on the surface of the material. The adsorbent in the present invention has both microporous and mesoporous structures.

[0081] Taking Example 3 as an example, the elemental composition and chemical state of δ-Bi2O3, MOF-808 and 60-Bi / M were determined by XPS. The results are as follows: Figure 1 (d)- Figure 1 As shown in (c), the two peaks at 159.4 eV and 164.7 eV are attributed to Bi 4f 7 / 2 and Bi4f 5 / 2 , confirms Bi 3+ is the main species in δ-Bi2O3. The two peaks at 182.9eV and 185.3eV are attributed to Zr 3d 5 / 2 and Zr 3d 3 / 2 . Compared with δ-Bi2O3 and MOF-808, the peaks of Bi 4f and Zr 3d in 60-Bi / M move in opposite directions, which is mainly due to the migration of free electrons on the sample surface caused by their different Fermi levels. From the direction of binding energy movement, it can be determined that the electrons mainly migrate from MOF-808 to δ-Bi2O3, which confirms that the heterogeneous interface is very tightly bound. The existence of OV was further explored by EPR. Figure 1 In (f), the EPR spectra of δ-Bi2O3 and the embodiment show a clear signal at g = 2.003, which strongly confirms the existence of OV, which can provide active adsorption sites, thereby facilitating the improvement of the adsorption capacity of iodine.

[0082] Taking Example 3 as an example, the morphology and surface composition of δ-Bi2O3, MOF-808 and 60-Bi / M were determined by SEM, TEM, SAED and HRTEM-EDS. Figure 2In (a), the synthesized MOF-808 is octahedral in shape with a particle size of 1 μm-2 μm. Figure 2 (b) is the morphology of δ-Bi2O3; the scanning electron microscope image of Example 3, as shown in FIG. Figure 2 As shown in (c), it can be observed that there is a uniform layer of nanoparticles on the surface of MOF-808. Figure 2 (d)- Figure 2 In (f), some lattice edges belonging to δ-Bi2O3{111} can be observed; in addition, clear diffraction rings corresponding to δ-Bi2O3 are observed in SAED mode; finally, HRTEM-EDS (e.g. Figure 2 (g)- Figure 2 (k) Bi, O, C and Zr can be clearly observed on the sample surface. It can be seen that the method of the present invention achieves uniform growth of δ-Bi2O3 on the surface of MOF-808.

[0083] In order to explore the effects of δ-Bi2O3, MOF-808 and the embodiment I - The adsorption capacity of α-hydroxy-1-nitropropene was tested by isothermal adsorption experiments. Figure 3 As shown in (a), with the initial I - With the increase of concentration, the adsorption capacity of the sample gradually increases. The equilibrium maximum adsorption capacities of MOF-808, 40-Bi / M, 50-Bi / M, 60-Bi / M, 70-Bi / M and δ-Bi2O3 are 64 mg / L, 115 mg / L, 159 mg / L, 191 mg / L, 209 mg / L and 167 mg / L, respectively. In the adsorbent of the present invention, as δ-Bi2O3 increases, the adsorption capacity of the adsorbent of the embodiment also increases. It is obvious that the adsorption capacity in the embodiment is mainly contributed by δ-Bi2O3. The improvement of the adsorption capacity of the adsorbent of the present invention is mainly due to the uniform loading of δ-Bi2O3 on the surface of MOF-808, which helps to expose the active sites. However, it is worth noting that as the amount of δ-Bi2O3 increases, its contribution to the adsorption capacity gradually decreases. This is mainly due to the fact that the excess δ-Bi2O3 is wrapped on the surface of MOF-808, increasing the agglomeration effect and thus reducing the exposure of the adsorption sites. Therefore, the mass ratio of bismuth trioxide to (zirconium-based metal organic framework + bismuth trioxide) is 40%-70%. The Langmuir model and the Freundlich model were used to evaluate the effects of δ-Bi2O3, MOF-808 and the embodiment on the adsorption capacity of I -The adsorption forms of MOF-808, 40-Bi / M, 50-Bi / M, 60-Bi / M, 70-Bi / M and δ-Bi2O3 were 77 mg / L, 129 mg / L, 176 mg / L, 202 mg / L, 220 mg / L and 169 mg / L, respectively. By comparing the correlation coefficient (R2), the fitting results of δ-Bi2O3 and the embodiment are more consistent with the Langmuir model, which shows that δ-Bi2O3 and the embodiment have good adsorption performance. - The adsorption of MOF-808 is monolayer adsorption, and the surface is uniform. However, the fitting results of MOF-808 are closer to the Freundlich model, indicating that MOF-808 has a good adsorption performance on I - The adsorption is a multi-layer adsorption.

[0084] The adsorption kinetics of δ-Bi2O3, MOF-808 and Example I - The adsorption rate of Figure 3 As shown in (b), at 10 minutes, the adsorption amount of δ-Bi2O3 accounts for about 78% of the total adsorption capacity, and its adsorption rate is much higher than that of MOF-808. This is partly due to the I - The higher concentration is due to the fact that the active sites in the pre-adsorbed phase are not occupied. In addition, the self-sufficient oxygen vacancies (OV) of δ-Bi2O3 also contribute to the increase of I - As expected, the introduction of δ-Bi2O3 improved the adsorption rate of Example 1. The pseudo first-order model and pseudo second-order model were used to evaluate the adsorption of δ-Bi2O3, MOF-808 and Example 1. - By comparing the fitting correlation coefficient (R2), the fitting results of δ-Bi2O3 and the embodiment are more consistent with the pseudo-second-order model, which indicates that δ-Bi2O3 and the embodiment have good adsorption performance on I - The adsorption process of MOF-808 belongs to chemical adsorption. The fitting results of MOF-808 are more consistent with the pseudo-first-order model, which confirms that MOF-808 has a good adsorption effect on I - The adsorption is mainly physical adsorption, and in the embodiment of the present invention, the physical adsorption capacity of the adsorption can be further improved by introducing the zirconium-based metal organic framework.

[0085] In order to explore the synergistic removal of I by photooxidation-adsorption - The photocatalytic effect was investigated. Figure 3 As shown in (c), after 5 hours of adsorption in the dark, a xenon lamp (300W) was turned on to simulate visible light. - The photooxidation effect of MOF-808, 40-Bi / M, 50-Bi / M, 60-Bi / M, 70-Bi / M and δ-Bi2O3 on I -The photo-oxidation effect of the embodiment is converted into iodine elemental amount of 7.5mg / g, 43mg / g, 54mg / g, 106mg / g, 73mg / g and 42mg / g respectively. - The photooxidation effect of MOF-808 is significantly better than that of MOF-808 and δ-Bi2O3. This strongly confirms that a heterostructure is constructed between MOF-808 and δ-Bi2O3, which promotes the migration of photogenerated carriers, thereby facilitating the oxidation of iodide ions and converting iodine ions into elemental iodine. At the same time, when the mass percentage of δ-Bi2O3 reaches 70%, the photooxidation effect shows a downward trend. On the one hand, the excess δ-Bi2O3 aggravates the agglomeration effect and affects the exposure of the reaction sites; on the other hand, the excess δ-Bi2O3 reduces the separation efficiency of carriers, thereby reducing the photooxidation effect. The photooxidation effect can be further quantified by the first-order kinetic equation, such as Figure 3 (d) is shown. MOF-808, 40-Bi / M, 50-Bi / M, 60-Bi / M, 70-Bi / M and δ-Bi2O3 versus I - The photooxidation rates (K) of MOF-808, 60-Bi / M and 60-Bi / M are 12.09 and 3.17 times higher than those of MOF-808 and δ-Bi2O3, respectively. It can be seen that the embodiments of the present invention have a good photooxidation rate, which is conducive to the adsorption of iodine ions.

[0086] The reaction solution was tested to explore the photooxidation-adsorption synergistic effect on I - The actual removal of the solution after the reaction was diluted and the I2 concentration was measured. Figure 3 As shown in (e), the residual I2 in the solution after the reaction of MOF-808, 40-Bi / M, 50-Bi / M, 60-Bi / M, 70-Bi / M and δ-Bi2O3 was approximately 0.7 mg / g, 4 mg / g, 7 mg / g, 10 mg / g, 9 mg / g and 39 mg / g, respectively. The percentage of I2 remaining in the photo-oxidation effect was 9.3%, 9.3%, 12.9%, 9.4%, 12.4% and 92.3%, respectively. Therefore, the amount of iodide ions actually removed by MOF-808, 40-Bi / M, 50-Bi / M, 60-Bi / M, 70-Bi / M and δ-Bi2O3 through photo-oxidation-adsorption was 70 mg / g, 154 mg / g, 206 mg / g, 287 mg / g, 272 mg / g and 170 mg / g, respectively. In addition, δ-Bi2O3 has a significant effect on I -The photooxidation amount of MOF-808 is greater than that of MOF-808. Most of I2 cannot be adsorbed in δ-Bi2O3. This is mainly because the adsorption sites on the surface of δ-Bi2O3 are filled in the dark adsorption stage, which makes δ-Bi2O3 unable to further adsorb iodine. The internal pores of MOF-808 in the embodiment structure of the present invention provide sufficient adsorption sites for I2. Therefore, the introduction of MOF can solve the problem of I - The problem of photooxidation and the actual removal of the oxidation products.

[0087] The initial pH value of the solution plays an important role in both the adsorption and photooxidation processes. In weakly acidic and weakly alkaline environments, the photooxidation-adsorption synergistic effect (taking Example 3 as an example, 60-Bi / M) removed I - The results are as follows Figure 4 (a) As shown. During the photooxidation process, δ-Bi2O3 will generate Bi4O5I2 after adsorbing iodine. In a weakly alkaline environment, 60-Bi / M has a strong effect on I - The adsorption efficiency of Bi4O5I2 is significantly reduced. This is mainly because the adsorption product (Bi4O5I2) will react with OH in the alkaline solution. - Reaction occurs to generate δ-Bi2O3 ( ); In a weakly acidic environment, the adsorption efficiency is improved, which is due to the H + The byproduct OH - The combination reduces the decomposition of Bi4O5I2, which is beneficial to the adsorption of iodine ions. In addition, the influence of pH value on the experiment was further explored by detecting the Zeta potential of 60-Bi / M. Figure 4 As shown in (b), the Zeta potential of 60-Bi / M is 19.1 mV, 11.7 mV, 5.2 mV, -5.9 mV and -10.4 mV in environments with pH values ​​of 3, 5, 7, 9 and 11, respectively. In a weakly acidic environment, the zeta potential of 60-Bi / M is positive, which promotes the interaction between 60-Bi / M and I - This also verifies that the adsorption effect of the adsorbent of the present invention on iodine can be further improved in a weak acid environment. Therefore, the adsorbent of the present invention is suitable for adsorbing iodine ions in a weak acid environment.

[0088] In order to explore the effect of 60-Bi / M on I - Competitive ion experiments were performed to determine the adsorption selectivity of Figure 4 As shown in (c), in NO3 - , Cl - 、SO4 2- and CO3 2- When present, 60-Bi / M to I -The adsorption efficiency of 60-Bi / M I - Adsorption of NO3 - , Cl - and SO4 2- The impact is small, mainly because NO3 - and SO4 2- It is an acidic ion, δ-Bi2O3 and I - The ΔG of the reaction is less than that of Cl - ; 60-Bi / M to I - The adsorption of CO3 2- This is mainly due to the fact that CO3 2- It is easily hydrolyzed in water to generate OH - On the one hand, OH - will intensify the reverse reaction of Bi4O5I2; on the other hand, alkaline environment will lead to the - Electrostatic repulsion is formed between them, thus interfering with I - Therefore, it was further verified that the acidic environment was beneficial to improve the adsorption effect of the adsorbent. - The adsorption of 60-Bi / M was affected, which would further affect the formation of I2 under photooxidation. - The removal is highly selective. The adsorbent in this case is suitable for adsorbing iodide ions in an environment with acidic ions.

[0089] Gamma-ray irradiation was performed on δ-Bi2O3, 60-Bi / M, and MOF-808 to evaluate the radiation effects of radioiodine on the samples. Figure 4 (d)- Figure 4 As shown in (e), the iodine adsorption capacity of δ-Bi2O3 and 60-Bi / M did not change significantly after gamma-ray irradiation. The XRD patterns of δ-Bi2O3 and 60-Bi / M did not change significantly before and after irradiation, indicating that irradiation had no significant effect on the crystal structure of δ-Bi2O3 and 60-Bi / M. However, after gamma-ray irradiation, the I - The adsorption capacity decreased by 13%. In addition, the characteristic peak at 8.84° in the XRD spectrum of MOF-808 also slightly attenuated, which may be due to the fact that the chemical bonds in the internal molecules of MOF-808 were affected by gamma rays. In general, δ-Bi2O3, 60-Bi / M and MOF-808 were affected by radioactive I - The effect of radiation was limited. The stability of 60-Bi / M after adsorption was evaluated by soaking the samples in water and ultrasonic treatment, e.g. Figure 4As shown in (f), after immersion (24 hours) and ultrasound (30 minutes), 60-Bi / M will have a small amount of point leaching after adsorption equilibrium. This is mainly due to the desorption of iodide by the physical adsorption of MOF-808, but overall, the adsorption of iodine by 60-Bi / M is relatively stable.

[0090] In order to further study the effects of δ-Bi2O3 and MOF-808 on I - The photo-oxidation adsorption mechanism of 60-Bi / M was investigated and the adsorption products were analyzed. The crystal structure of 60-Bi / M before and after photo-oxidation adsorption was analyzed by XRD spectrum. Figure 5 As shown in (a), some obvious Bi4O5I2 characteristic peaks appeared in the XRD spectrum after adsorption. At the same time, the intensity of the δ-Bi2O3 characteristic peak was significantly weakened. It is well known that Bi4O5I2 is composed of δ-Bi2O3 and I - Therefore, in the adsorption stage, Bi4O5I2 is the product of δ-Bi2O3, while in the photooxidation stage, iodine ions are photooxidized to generate iodine, and δ-Bi2O3 does not form new products. In addition, the intensity of the characteristic peak belonging to MOF-808 is weakened, which is attributed to the absorption of MOF-808 on I - adsorption.

[0091] XPS further analyzed the chemical state of the samples before and after photooxidation-adsorption. Figure 5 (b) and Figure 6 As shown in Figure 2, a comparison of Example 3 before photo-oxidation adsorption (60-Bi / M) and after photo-oxidation adsorption (60-Bi / MI-light) revealed that the binding energies of the Bi 4f and Zr 3d peaks increased by 0.4 eV and 0.3 eV, respectively, which confirmed that 60-Bi / M and I - An adsorption reaction occurred. Figure 5 In (c), the peak intensities of OVs and Zr-OH are significantly weakened after photooxidation-adsorption, indicating that OVs and Zr-OH sites are active sites for the adsorption of iodide. Figure 5 As shown in (d), the peaks at 631.1 eV and 619.5 eV in the spectrum of 60-Bi / MI (the product of 60-Bi / M after iodine adsorption) are the adsorbed I - In the 60-Bi / MI spectrum, the peaks at 632.7 eV and 631.2 eV are I2, which confirms that I - It is photooxidized to I2. It is worth noting that δ-Bi2O3-I - There is no I2 peak in the spectrum (the product after δ-Bi2O3 adsorbs iodine), which indicates that MOF-808 is the only adsorption unit of I2. In addition, Raman spectroscopy also conducted an in-depth study on the adsorption form of MOF-808 and I2. Figure 5(e) at 110 cm -1 and 170cm -1 The nearby peaks are attributed to I3 - and I2. I3 was not detected in the Raman spectrum of the adsorption stage - and I2 peaks, which confirms that I2 is mainly produced by photooxidation. The vibration frequency of II increases from 170 cm -1 Move to 110cm -1 , is due to the charge transfer and interaction between the adsorbent and the σu* orbital of I2. In the initial stage of photooxidation, the generated I2 is mainly in the form of I3 - adsorbed in the form of MOF-808. As the I2 produced by photooxidation increases, I2 mainly accumulates in the pores of MOF-808. The changes in OV during the photooxidation-adsorption process were studied by EPR. Figure 5 In (f), the OVs signal is significantly weakened after adsorption, but not significantly after photooxidation. This indicates that the consumption of OVs is mainly due to the absorption of δ-Bi2O3 on I - The EPR results are consistent with the XPS results.

[0092] The morphology and surface composition of 60-Bi / M after photo-oxidation adsorption were observed by SEM, TEM, SAED and HRTEM-EDS. The results of SEM showed that the morphology of MOF-808 did not collapse significantly after photo-oxidation adsorption, such as Figure 5 (g) At the same time, lattice fringes matching the {312} of Bi4O5I2 were observed on the surface of δ-Bi2O3, as shown in Figure 5 (h) As shown. In the SAED mode, clear diffraction rings corresponding to Bi4O5I2 were also observed, such as Figure 5 (i) In addition, the I element can be clearly observed on the sample surface by HRTEM-EDS, as shown in Figure 5 (j) As shown above, on the one hand, under the action of photo-oxidation adsorption, I - It is stably adsorbed on the surface of δ-Bi2O3 in the form of Bi4O5I2. - Photooxidized to form I2, which then forms I3 inside MOF-808 - , or accumulated in the pores of MOF-808 in the form of I2.

[0093] In summary, δ-Bi2O3 / MOF-808 synthesized by in situ growth method has high I - Removal capacity. 60-Bi / M to I -The photo-oxidation-adsorption removal effect of MOF-808 was the best (287 mg / g). Among them, the removal rate of photo-oxidation was 32% (96 mg / g). MOF-808 as a carrier solved the agglomeration problem of δ-Bi2O3, thereby exposing more adsorption sites. In summary, δ-Bi2O3 / MOF-808 has excellent removal performance and rich oxidation pathways, and is effective in selectively removing radioactive I - It has good environmental application prospects.

[0094] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.

[0095] It should also be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

[0097] References: [1]Yang, P., et al., Metal–Organic Frameworks Bearing Dense AlkylThiol for the Efficient Degradation and Concomitant Removal of Toxic Cr(VI).Langmuir, 2019. 35(49): p. 16226-16233. doi.org / 10.1021 / acs.langmuir.9b03057.

Claims

1. A photo-oxidative adsorbent for the removal of radioactive iodide, characterized in that: The adsorbent comprises a zirconium-based metal organic framework, and bismuth trioxide is uniformly deposited on the surface of the zirconium-based metal organic framework.

2. The photo-oxidation adsorbent according to claim 1, characterized in that: By mass, bismuth trioxide / (zirconium-based metal organic framework+bismuth trioxide) is 40%-70%.

3. The method for preparing the photo-oxidative adsorbent for removing radioactive iodide according to any one of claims 1 to 2, characterized in that: The preparation method comprises: The zirconium-based metal organic framework and the bismuth source are dissolved and dispersed, and then a glycine solution is added dropwise to obtain a mixed solution. The mixed solution is subjected to a hydrothermal reaction and washed to obtain an adsorbent for depositing bismuth trioxide on the surface of the zirconium-based metal organic framework.

4. The preparation method according to claim 3, characterized in that: After the zirconium-based metal organic framework and the bismuth source are dissolved and dispersed, the molar concentration of the bismuth source in the dispersed solution is 1 mmol / 20 mL based on the bismuth ions in the bismuth source.

5. The preparation method according to claim 3, characterized in that: By mass, bismuth trioxide / (zirconium-based metal organic framework+bismuth trioxide) is 40%-70%.

6. The preparation method according to claim 3, characterized in that: The bismuth source includes one or more of bismuth nitrate and bismuth nitrate pentahydrate; The zirconium-based metal organic framework is MOF-808.

7. The preparation method according to claim 3, characterized in that: The molar concentration of glycine in the glycine solution is 1 mmol / 10 mL.

8. The preparation method according to claim 3, characterized in that: The volume ratio of the solution in which the zirconium-based metal organic framework and the bismuth source are dissolved and dispersed to the glycine solution is 4:

3.

9. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 130°C-150°C, and the time of the hydrothermal reaction is 23h-25h.

10. Use of the photo-oxidative adsorbent for removing radioactive iodide according to any one of claims 1 to 2 or the photo-oxidative adsorbent prepared by the preparation method according to any one of claims 3 to 9 in adsorbing iodine.

Citation Information

Cited By

  • Lignin organic framework composite material, preparation thereof and application of lignin organic framework composite material in halogen adsorption

    CN121136123A